VARIASI PERTUMBUHAN UDANG WINDU (Penaeus monodon) DAN IKAN BANDENG (Chanos chanos) PADA BUDIDAYA POLIKULTUR TAMBAK WANAMINA DENGAN JENIS VEGETASI MANGROVE YANG BERBEDA DI KOTA SEMARANG - Rini Budihastuti (JURNAL LITBANG PROVINSI JAWA TENGAH, 2014)
The effort to support silvofishery application is needed to maintain the sustainability of coastal resources utilization. But, inappropriate knowledge of the aquaculturists and lack of evidence concerning the application of silvofishery in aquabusiness became the major problems of the effort. This research aimed to study the effect of silvofishery system with different mangrove specieses to the growth of Tiger shrimp and Milkfish. The research was conducted through experiment involving Avicennia marina and Rhizophora mucronata and control pond (without mangrove vegetation) as comparison. While the cultured biota including Tiger shrimp and Milkfish with polyculture system. The research was conducted with 2 replication for 3 months (90 days). The observation factors including the growth of culture biota including total length, standart lengt and weight. The result showed that the growth of Tiger shrimp was optimum in silvofishery pond involving Rhizophora mucronata. While the growth of Milkfish was optimum in silvofishery pond invlving Avicennia marina. Total length of Tiger shrimp from the experiment ranged from 10,3 – 19,6 cm at control pond; 10,3 – 20,6 cm at Avicennia pond; and 17,5 – 19,8 cm at Rhizophora pond. While standart length of Tiger shrimp ranged from 4,0 – 7,5 cm at control pond; 3,5 – 15,5 cm at Avicennia pond and 7,3 – 8,0 cm at Rhizophora pond. While the weight of Tiger shrimp ranged from 5 – 60 gr at control pond; 15 – 70 gr at Avicennia pond and 50 – 75 gr at Rhizophora pond. Measurement on the growth of Milkfish showed the range of total length from 11,0 – 28,5 cm at control pond; 22,3 – 32,0 cm at Avicennia pond and 17,5 – 28,5 at Rhizophora pond. While standart length of Milkfish ranged from 4,0 – 20,7 cm at control pond; Avicennia pond range from 17,8 – 25,5 cm; and Rhizophora pond ranged from 13,9 – 23,4 cm. Average weight of Milkfish ranged from 5 – 140 gr at control pond; 90 – 240 gr at Avicennia pond and 50 – 250 gr at Rhizophora pond.